From Binary to Rich Dialectics: The Revolt of the Fishermen and Mauser - Koutsourakis, Angelos (Cinema: Journal of Philosophy and the Moving Image, 2016)
Dialectics constitutes one of Marx’s key theoretical formulations. For Marx, the dialectic stands for a method of negation that reveals the mediated aspect of what appears to be evident and immediate. While Marx’s view of the dialectic goes beyond Hegelian binaries, the prototype of dialectical cinema as typified in the films of Eisenstein relies on the employment of binaries, whose collision produces a synthesis that offers a concrete hermeneutical schemata. Although such a paradigm offers an elementary introduction to the Marxist approach to history, it ignores the richness of Marxist dialectics and offers a somehow mechanistic understanding both of the historical process as well as of cinema’s ability to employ the dialectical method productively. This article explores the shift from a binary to a rich dialectic by focusing on two case studies: Erwin Piscator’s The Revolt of the Fishermen (1934) and Philippe Vincent’s adaptation of Heiner Müller’s Mauser (1999). Though both films are grounded in a dialectical staging reliant on fragmented sequences that generate associations in place of diegetic linearity, they differ in their employment of the dialectical method. In offering a comparative reading of these two films, the article intends to open up different ways of thinking about cinema and dialectics so as to redeem the dialectical method as a valid means of addressing political questions in the present.